Parent–child talk about motion: Links to children's development of motion event language. Issue 4 (August 2013) - Hohenstein, Jill
This study investigated the motion event language children and their parents engaged in while playing a board game. Children are sensitive to differences in manner and path at infancy, yet adult-like motion event expression appears relatively late in development. While multiple studies have examined how exposure to parent speech generally relates to very young children's language, none looks at motion event language and learning in 3- to 7-year-olds. This study aimed to examine the opportunities for children to learn motion event language through engaging with their parents, using a constructivist view of language learning. Parent–child conversation of Spanish-speaking (21) and English-speaking (24) families was examined for lexical and syntactic differences in motion event expressions. Results demonstrated English-speaking parents used more manner verbs and Spanish-speaking parents used more specific path verbs. English-speaking parents also used more general path verbs than did Spanish speakers. These differences mapped onto children's production of motion event language. Parental speech may provide the potential for children to gradually learn about motion event language typology.